Intrusion. A look at Franz Kafka’s literary workshop - Francesco Galofaro (E|C, 2024)
The present paper will show how semiotics can discuss the condition of possibility of philology and genetic critics. The case study consists of some literary exercises by Franz Kafka. A recurring exercise in Kafka’s Diaries consists of rewriting a passage, often extending it with respect to its original version. Greimas’ generative trajectory allows to describe a constant narrative structure, that of intrusion, linking the different fragments. Kafka uses it several times by varying the elements of the semio-discursive level. Starting from this description, it is possible to distinguish different types of semiotic work performed by the enunciator to articulate and coordinate the planes of expression and content. Finally, these rewritings presuppose a dividual model of enunciation, whose subject is split into a pragmatic instance that selects and projects the elements on the level of the phrase and a second judgmental, cognitive instance that criticizes and amends the work of the previous one.